Эффекты сезонной и полугодовой аномалий в вариациях концентрации электронов в максимуме области F₂ ионосферы на разных фазах цикла солнечной активности - Ляшенко, Михаил Владимирович; Ляшенко, Нина Сергеевна (My University, 2016)
Представлены результаты экспериментальных исследований вариаций концентрации электронов в максимуме области F₂ ионосферы по данным ионозонда “Базис”. Выполнен анализ и физическая интерпретация эффектов сезонной и полугодовой аномалий в вариациях концентрации электронов Nm на разных фазах цикла солнечной активности. Приведены результаты сравнительного анализа расчетов Nm по глобальной модели ионосферы IRI-2012, региональной модели ионосферы CERIM IION и экспериментальными данными ионозонда “Базис”.

Results of experimental investigations of variation of electron concentration in the maximum of F₂ region of ionosphere on ionosonde “Basis” data are presented. Analysis and physical interpretation of seasonal and semi-annual anomaly effects in the Nm electron concentration variations on different phases of the solar activity cycle were carried out. Results of the comparative analysis of the Nm calculations from IRI-2012 global ionospheric model and CERIM IION regional model of ionosphere and the ionosonde “Basis” experimental data are presented.
The effects of seasonal and semi-annual anomalies in the variation of the electron density at the maximum of the F₂ region of the ionosphere at different phases of the solar activity cycle
Keywords: геофизика; модель ионосферы; ионозонд; ионосферная плазма; гелиогеофизическая обстановка; electron concentration; seasonal anomaly; semi-annual anomaly; model of ionosphere; solar activity cycle